Multiwavelength study of RCW 108 as a massive star forming region - Romero, Gisela Andrea (2008)
NGC 6193 is an open cluster embedded in an Hii region (RCW 108, Rodgers et al. 1960) located 15 0 eastwards of NGC 6188. The later is a bright rimmed cloud that stretches over 30 0 in the north-south direction, and marks the interface between RCW 108 and nearby dark clouds. RCW 108 is being powered by the multiple O-type star systems, namely HD 150135-HD 150136 (Niemela & Gamen 2005) in the core of NGC 6193. The UV photons emitted by these stars may drive photoinization-induced shocks into the nearby molecular clouds, possibly originating the well studied infrared cluster RCW108- IR (Comerón et al. 2005, and references therein). In this work we describe the morphology of the distribution of the photoionized and shock-excited gas based on Hα, [O III] and [S II] images, 13CO observations, and infrared data (2MASS, MSX).